1991
DOI: 10.1042/bj2730787
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Escherichia coli, purification and characterization of two mammalian thioesterases involved in fatty acid synthesis

Abstract: Thioesterase I, a constituent domain of the multifunctional fatty acid synthase, and thioesterase II, an independent monofunctional protein, catalyse the chain-terminating reaction in fatty acid synthesis de novo at long and medium chain lengths respectively. The enzymes have been cloned and expressed in Escherichia coli under the control of the temperaturesensitive A repressor. The recombinant proteins are full-length catalytically competent thioesterases with specificities indistinguishable from those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…6C) (28) and E. coli (17). Together, these results from interkingdom switching of fatty acid synthase components further the idea that plant and bacterial type II fatty acid synthases are functionally related and are distinct from type I.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…6C) (28) and E. coli (17). Together, these results from interkingdom switching of fatty acid synthase components further the idea that plant and bacterial type II fatty acid synthases are functionally related and are distinct from type I.…”
mentioning
confidence: 81%
“…Thus, plant and prokaryotic fatty acid synthases resemble each other in structure, and the plant fatty acid synthase resides in the chloroplast (23), which is considered to be of prokaryotic origin. Therefore, the structural similarities may be due to a common ancestry of plant and prokaryotic fatty acid synthases (14,17,20). Currently, it is not known whether type II protein components exist in a dissociated state or whether they are noncovalently combined in a discrete enzyme complex (7,10,20,32).…”
mentioning
confidence: 99%
“…These results suggest that Spot14 might augment release of fatty acids via the resident thioesterase domain of FASN. Naggert et al ( 65 ) showed that the resident thioesterase domain from FASN relies entirely on its covalent linkage to FASN for function, as the recombinant "free" thioesterase domain had no activity toward S-acyl-FASN. We speculate that Spot14 could foster a more productive interaction of the resident thioesterase domain with the acyl carrier domain of FASN to stimulate release of its fatty acid products.…”
Section: Spot14 Increases Fatty Acid Synthase Activity In Mecsmentioning
confidence: 99%
“…Such is the case for the multifunctional animal fatty acid synthase (8,(12)(13)(14)(15)(16). Additionally, the thioesterase domain of the fatty acid synthase has been expressed as an independent catalytically active recombinant protein in E. coli (3,17) demonstrating that domains of the fatty acid synthase may be capable of folding correctly into catalytically competent proteins out of context of the full-length polypeptide. In this study, for the first time, a domain of the fatty acid synthase has been expressed as a recombinant The results of this study provide strong evidence implicating His-683 in the catalytic mechanism of the malonyl-/acetyltransferase.…”
mentioning
confidence: 99%
“…Thus, each of the catalytic components of the fatty acid synthase is envisioned to be an independently folded domain. However, as yet, only one of the components of the animal fatty acid synthase, the thioesterase, has been expressed as an independent, catalytically active recombinant protein (3). In this study we sought to develop a system for expression of the malonyl-/acetyltransferase domain of the animal fatty acid synthase that would allow us to define the boundaries of this domain and ultimately would facilitate a detailed analysis of the catalytic mechanism of the enzyme through the construction and characterization of specific mutants.…”
mentioning
confidence: 99%